Legal Construction of Academic Draft Obligations in the Formation of Regional Regulations - Cynthia Hadita (International Forum of Researchers and Lecturers, 2024)
This study examines the legal construction of the obligation to prepare Academic Draft s in the process of forming regional regulations in Indonesia. Academic texts have a strategic role as a scientific and rational basis to ensure that the Regional Regulations produced are in accordance with the needs of the community, based on the principles of good regulation formation, and do not contradict higher legal norms. This study uses a normative juridical method with a statutory approach and conceptual analysis to identify the relevance, implementation, and challenges in the implementation of Academic Draft obligations. The results of the study show that the obligation to prepare Academic Draft s has been regulated in laws and regulations, but its implementation is often faced with various obstacles, such as low technical understanding, limited budget allocation, and lack of expert involvement. Therefore, it is necessary to strengthen regulations and increase institutional capacity to ensure a more participatory, transparent, and accountable process for the formation of regional regulations. This research is expected to contribute to the development of policies that support the formation of quality and responsive regional regulations to the needs of the community.